Assessing awareness of halal food premises: issues and strategic solutions - Mohd Sharifuddin, Nur Fadiah Qistina Audi; Zulkifli, Nur Masitah; Yahaya, Amiratul Munirah; Mohamad, Rusni (Universiti Teknologi MARA (UiTM), Malaysia, 2026)
In the contemporary era, the food and beverage industry grown rapidly. This can be observed through the rise in the number of premises that have been established currently. This growth provides consumers many types of options. However, this industry is always facing thousands of problems regarding the disobedience of the halal and haram concept, whether during the preparation of the food or its consumption. Therefore, this study aims to measure the awareness among society towards the halal status of premises, analyse the factors of premises not having halal certification and to identify the solution to encourage premises owners to apply for halal certificates. This study used a mixed methods approach, combining quantitative and qualitative methods. A survey was conducted on 50 respondents by using Google Forms while qualitative data were obtained through the analysis of journals and articles. The findings show that most of the respondents were concerned about the halal certification of the restaurant. Majority also believe that a sign of ‘no pork’ and ‘no alcohol’ do not guarantee halal compliance due to there being other factors that can influence the halal status. Additionally, three major factors of premises were founded as contributing to the absence of halal certification, which are the strict procedures required by Department of Islamic Development Malaysia (JAKIM), the complicated documentation process and financial problems. As a result, effective solutions are proposed including applying halal certification through MYeHALAL, ensuring raw materials used in the premises have a halal certification or supporting documents from the authority, sending the internal staff to halal training provided by JAKIM to avoid hiring outsiders as halal executives and give a financial support to the premises that want to apply for halal certification.